2006
DOI: 10.1177/0361198106195100113
|View full text |Cite
|
Sign up to set email alerts
|

Econometric Analysis of U.S. Airline Flight Delays with Time-of-Day Effects

Abstract: An econometric model of average daily delay is formulated and estimated to analyze flight delay in the U.S. domestic system. The model considers the effects of arrival queuing, volume, terminal weather, en route weather, seasonal effects, and secular effects. In particular, the time-of-day effects of arrival queuing, the effects of scheduled arrivals, and the interaction between scheduled arrivals and weather conditions are investigated. The estimation results suggest that ( a) queuing has a greater delay impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 3 publications
0
16
0
Order By: Relevance
“…Hotels therefore should be rewarded not only for producing good outputs (for example, revenue) but also for reducing their negative outputs. Research in other industries, for instance, has included 'pollution' when measuring the performance of industries, 'complications in operational procedure' when measuring the performance of hospitals and 'flight delays' when measuring the performance of airports (Tucker, 2004;Zaim, 2004;Hsiao and Hansen, 2006). All these are negative outputs that can affect the production process.…”
mentioning
confidence: 99%
“…Hotels therefore should be rewarded not only for producing good outputs (for example, revenue) but also for reducing their negative outputs. Research in other industries, for instance, has included 'pollution' when measuring the performance of industries, 'complications in operational procedure' when measuring the performance of hospitals and 'flight delays' when measuring the performance of airports (Tucker, 2004;Zaim, 2004;Hsiao and Hansen, 2006). All these are negative outputs that can affect the production process.…”
mentioning
confidence: 99%
“…Although the pattern varies with the airport, in general, the marginal cost of delay increases until a certain time in the afternoon, after which time the airport begins absorbing more of the delay. This effect is also shown by Tu (14) and Hsaio and Hansen (15), as they examined flight delays through econometric models, estimated the marginal cost of delay in relation to later delays, and demonstrated that earlier delays are more costly, without considering explicitly the propagation effects.…”
mentioning
confidence: 62%
“…The authors of Hsiao and Hansen (2006) formulate a model of the average daily flight delay, considering factors including queuing, especially time-of-day effects of arrivals, and weather at airports and on flights' routes. Through queuing theory, the authors find that a certain amount of queuing delay in the morning causes a much bigger impact on average daily delay than the same amount of delay in the evening does.…”
Section: Creating Robust Schedulesmentioning
confidence: 99%